Peran Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas Perdagangan Kota Medan - Fitri Sagita; Waizul Qarni (VISA: Journal of Vision and Ideas, 2022)
This study aims to analyze the role of work motivation and work environment in employee performance at the Medan City Trade Office. The method used in this research is a detailed qualitative method that leads to an in-depth description and description of the actual situation in the field. This study uses an open interview technique that is shown directly to employees of the trade department in the field of development and foreign trade. The results of this study indicate that the role of work motivation and work environment in employee performance at the Medan City Trade Office in the field of development and foreign trade affects the performance of employees. This is shown by the attitude of kinship and mutual assistance in carrying out tasks and discussing the program in deliberation. So that the increase in class, promotion and the results of their successful performance increase the motivation of employees so that they have good performance. Keywords: Performance, Work Environment, Motivation